Potential Analysis of the Application of Fuzzy Logic in the Optimization of Pak Choi Hydroponic Cultivation: A Literature Study on Plant Growth Support System - Putri Jasmin; Anton Wira Pratama; Mahatmadi Ariq Mayangkara; Muhamad Reza Zulva Pohan; Allegra Alif Rahman; Inna Novianty; Nanda Octavia; Ivan De Nerol (Journal of Applied Science, Technology & Humanities | JASTH, 2024)
The rapid urbanization and increasing population density in Indonesia have led to a reduction in available land for traditional agriculture, particularly in urban centers. In response to this challenge, urban farming, including hydroponic cultivation, has emerged as a viable solution to meet the food needs of urban communities. This study explores the potential application of fuzzy logic in optimizing hydroponic cultivation practices, focusing on the growth of pak choi plants. Pak choi, a popular vegetable in Indonesia, offers numerous health benefits and is well-suited for hydroponic cultivation. By analyzing relevant literature, this research investigates the influence of water pH and temperature on pak choi plant growth and develops a fuzzy expert system based on Mamdani's method. The study prepares data on optimal temperature and pH ranges for pak choi cultivation and establishes fuzzy sets for water temperature, water pH level, and plant height. The findings provide insights into the effects of water pH and temperature on pak choi plant growth and demonstrate the potential of fuzzy logic in optimizing hydroponic cultivation practices. This research contributes to the advancement of agricultural technology and offers practical solutions for sustainable urban farming.